2005
DOI: 10.4049/jimmunol.175.2.685
|View full text |Cite
|
Sign up to set email alerts
|

The Synthetic Peptide Trp-Lys-Tyr-Met-Val-D-Met Inhibits Human Monocyte-Derived Dendritic Cell Maturation via Formyl Peptide Receptor and Formyl Peptide Receptor-Like 2

Abstract: Trp-Lys-Tyr-Met-Val-D-Met (WKYMVm) has been reported to stimulate monocytes, neutrophils, and dendritic cells (DCs). However, although WKYMVm has been reported to function as a DC chemoattractant, its role on DC maturation has not been examined. In this study, we investigated the effects of WKYMVm on human DC maturation. The costimulation of DCs with WKYMVm and LPS dramatically inhibited LPS-induced IL-12 production, CD86 and HLA-DR surface expression, and DC-mediated T cell proliferation. However, DC phagocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 48 publications
7
41
0
2
Order By: Relevance
“…Previous studies have demonstrated that WKYMVm stimulates a variety of intracellular signaling molecules; perhaps the best characterized function is its role in the MAPK pathway (48,49). In this study, we showed that FPR family activation by WKYMVm induces ERK, p38 MAPK, and JNK activation in human NK cells.…”
Section: Discussionsupporting
confidence: 48%
“…Previous studies have demonstrated that WKYMVm stimulates a variety of intracellular signaling molecules; perhaps the best characterized function is its role in the MAPK pathway (48,49). In this study, we showed that FPR family activation by WKYMVm induces ERK, p38 MAPK, and JNK activation in human NK cells.…”
Section: Discussionsupporting
confidence: 48%
“…F2L binds and activates the human G protein-coupled receptors FPRL-1 and FPRL2, members of the FPR family, in the low micromolar and low nanomolar range, respectively, and chemoattracts human monocytes and dendritic cells, which are known to express FPR, FPRL1 and -2, and FPR and FPRL2, respectively (1,4,5). F2L also inhibits LPS-induced dendritic cell maturation (6). These findings suggested that F2L might play a role in the initiation and/or regulation of immune responses, a hypothesis that may be tested in part by analyzing F2L receptors in animal models.…”
Section: F Ormylpeptide Receptor (Fpr)mentioning
confidence: 99%
“…When tested on monocytes and monocyte-derived DCs, F2L promotes calcium mobilization and chemotaxis (17). F2L inhibits the IL-12 production promoted by LPS in DCs and appears therefore to be an inhibitor of DC maturation (18).…”
Section: Formyl Peptide Receptor-like 2 Is Expressed and Functional Imentioning
confidence: 99%